The Effect of Marble Powder Additive at Different Ratios on the Radiation Absorption Parameters of Barite Based Concretes - SAVAŞ, Yasemin; BAŞARAN, Boğaçhan; ÇETİN, Betül (International Journal of Computational and Experimental Science and Engineering, 2023)
This article contains the results of an experimental study to investigate the radiation shielding effect as a result of adding crushed marble powder at different rates to baritebased concretes. The mixtures of the produced concretes were calculated according to TS 802. In 1st group concretes formed by 9x9x9 cm sized cube samples, cement and aggregate ratio were kept constant and marble and barite ratios were changed. In the 2nd group concretes, the cement and barite ratio were kept constant and the marble and aggregate ratios were changed. The linear attenuation coefficients have been measured at 1773 and 1332 keV for samples using a gamma spectrometer that contains a 3”x3” NaI (Tl) detector and connected to Multi-Channel Analyzer (MCA). Also, the correlation between linear attenuation coefficients and marble doped % for the photon energies was calculated and R2 was found to be 0.90 and above for all samples. In addition, these results have been used to calculate the half value layer (HVL) and mean free path (mfp) parameters. This study shows that the added of crushed marble powder contributes positively to the radiation absorption properties of barite added to concrete.